Prospects for the introduction of the concept of TQM (Total Quality Management) in higher educational institutions of Uzbekistan - Nigmonjon Pardayevich Azizov (Zien Journals, 2022)
The article analyzes the implementation of the requirements of the concept of total quality management in higher educational institutions of Uzbekistan.
Keywords: education; higher education; the concept of total quality management; system